ANALYSIS OF READINESS OF FUTURE TEACHERS TO FORM ENVIRONMENTAL PICTURE OF PRESCHOOLERS - Dombek, Svetlana; Lebedeva, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article deals with the problem of readiness of future teachers to form environmental picture of preschoolers. The authors define the notions «environmental culture», «environmental education»; draw conclusions about forming of notion «environmental culture» at the stage of preschool childhood and necessity of preparation of future teachers to forming of environmental picture of preschoolers.The analysis of empirical investigation of students' readiness to form environmental picture of preschoolers showed that the students understand the essence of environmental categories, navigate the content and forms of environmental work with the children, mark the necessity of practice in environmental education of preschoolers.The article is intended for public reading and for those who are interested in pedagogical research.